We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
71
1
avatar+1112 

Solve the following systems by any method.

 

4x + 7y = 6

9x - 2y = 49 

 

 

 

 

and

 

 

 

 

3x - y = 4

y = 2x -2

 Apr 30, 2019
 #1
avatar+101871 
+1

4x + 7y = 6

9x - 2y = 49 

 

Let's choose to eliminate y.....we can do this by multiplying the first equation by 2   and the second by 7.....do you see why this might work, SMM???.....so we have

 

8x + 14y = 12

63x - 14y = 343          add these   and notice that "y" disappears

 

71x  =  355       divide both sides by 71

x  = 5       

 

Can you take it from here and find y ???

 

 

 

3x - y = 4

y = 2x -2      easier than the first one......we have an explicit expression for y......so....sub the second equation into the first for y   and we have

 

3x - [ 2x - 2 ]  = 4       simplify

3x - 2x + 2  = 4

x + 2  = 4

x = 2

 

Sub this into the second equation to find y

 

cool cool cool

 Apr 30, 2019

18 Online Users

avatar
avatar